Contemporary review of prognostic markers of prostate cancer from a pathologist perspective - Elias, Martin; Bouchal, Jan; Kral, Milan; Kurfurstova, Daniela (Biomedical papers, 2025)
Prostate cancer is the most frequently diagnosed malignant tumour in men worldwide. To treat this condition, prognostic markers to distinguish indolent from aggressive disease, and biomarkers for metastatic forms are needed. From a pathologist's perspective, despite the plethora of emerging biomarkers, none to date has made its way into clinical practice. The need for prognostic and predictive markers following histological evaluation remains. This overview of some putative immunohistochemical and genetic markers reveals the pitfalls of biomarker research, notably verifiability, validity and interlaboratory comparison. Meta-analyses and extensive cooperation between pathology departments are a sine qua non. Codes of Best Practice such as the REMARK guidelines have been advocated as a path forward. Currently, the most widely used and validated prognostic marker remains the Gleason score. Ki67 along with PTEN are the most promising prognostic markers.
Keywords: prostate adenocarcinoma; Gleason score; prostate biopsy; radical prostatectomy; immunohistochemistry; prognostic and predictive markers